Market competition, R&D and firm profits in asymmetric oligopoly - Junichiro Ishida; Toshihiro Matsumura; Noriaki Matsushima (Osaka University, Institute of Social and Economic Research (ISER), 2010)
We investigate a Cournot model with strategic R&D investments wherein efficient low-cost firms compete against less efficient high-cost firms. We find that an increase in the number of high-cost firms can stimulate R&D by the low-cost firms, while it always reduces R&D by the high-cost firms. More importantly, this force can be strong enough to compensate for the loss that arises from more intense market competition: the low-cost firms' profits may indeed increase with the number of high-cost firms. An implication of this result is far-reaching, as it gives low-cost firms an incentive to help, rather than harm, high-cost competitors. We relate this implication to a practice known as open knowledge disclosure, especially Ford's strategy of disclosing its know-how publicly and extensively at the beginning of the 20th century.
Keywords: L13; O32; M21; 330; competition; oligopoly; R&D; heterogeneity; entry; Technischer Fortschritt; Markteintritt; Wettbewerb; Duopol; Theorie